Motif D of viral RNA-dependent RNA polymerases determines efficiency and fidelity of nucleotide addition - Yang, Xiaorong (2012)
Fast, accurate nucleotide incorporation by polymerases facilitates expression and maintenance of genomes. Many polymerases use conformational dynamics of a conserved α-helix to permit efficient nucleotide addition only when the correct nucleotide substrate is bound. This α-helix is missing in structures of RNA-dependent RNA polymerases (RdRps) and reverse transcriptases (RTs). Here we use solution-state NMR to demonstrate that the conformation of conserved structural motif D of an RdRp is linked to the nature (correct vs. incorrect) of the bound nucleotide and the protonation state of a conserved, motif-D lysine. Structural data also reveal the inability of motif D to achieve its optimal conformation after incorporation of an incorrect nucleotide. Functional data are consistent with the conformational change of motif D becoming rate limiting during and after nucleotide misincorporation. We conclude that motif D of RdRps and, by inference, RTs is the functional equivalent to the fidelity helix of other polymerases.